2022
DOI: 10.1002/ptr.7385
|View full text |Cite
|
Sign up to set email alerts
|

Lucidone inhibits autophagy and MDR1 via HMGB1/RAGE/PI3K/Akt signaling pathway in pancreatic cancer cells

Abstract: Gemcitabine (GEM) drug resistance remains a difficult challenge in pancreatic ductal adenocarcinoma (PDAC) treatment. Therefore, identifying a safe and effective treatment strategy for PDAC is urgent. Lucidone is a natural compound extracted from the fruits of Lindera erythrocarpa Makino. However, the role of lucidone in PDAC inhibition remains unclear. In addition, high-mobility group box 1 (HMGB1) and receptor for advanced glycation end products (RAGE) are involved in multidrug resistance protein 1 (MDR1) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In pancreatic cancer, an increasing body of evidence suggests that autophagy plays an essential role in triggering gemcitabine chemoresistance. 67,68 To investigate whether autophagy induced by substrate stiffness is involved in the chemoresistance of PANC-1 and MIA-PaCa2, the changes in the gene and protein expression levels of the ABC transporter family-related genes ABCC1, ABCC3, ABCC10, and ABCG2 were examined, by inhibiting or activating autophagy with rapamycin and chloroquine. Previous experimental results have shown that in PANC-1 and MIA-PaCa2 cells cultured on hydrogels, soft substrate group exhibited low autophagy level, while stiff substrate group showed high autophagy level.…”
Section: Resultsmentioning
confidence: 99%
“…In pancreatic cancer, an increasing body of evidence suggests that autophagy plays an essential role in triggering gemcitabine chemoresistance. 67,68 To investigate whether autophagy induced by substrate stiffness is involved in the chemoresistance of PANC-1 and MIA-PaCa2, the changes in the gene and protein expression levels of the ABC transporter family-related genes ABCC1, ABCC3, ABCC10, and ABCG2 were examined, by inhibiting or activating autophagy with rapamycin and chloroquine. Previous experimental results have shown that in PANC-1 and MIA-PaCa2 cells cultured on hydrogels, soft substrate group exhibited low autophagy level, while stiff substrate group showed high autophagy level.…”
Section: Resultsmentioning
confidence: 99%
“…Further experiments reveal that lucidone significantly inhibits the protein levels of HMGB1 and RAGE in GEM-resistant pancreatic cancer cells. In conclusion, lucidone promotes apoptosis in human pancreatic cancer cells through the HMGB1-RAGE axis ( 110 ) ( Figure 3 ).…”
Section: Hmgb1/rage Axis and Tumor Developmentmentioning
confidence: 94%
“…demonstrated that 4-AAQB downregulates autophagy through inhibition of the HMGB1/RAGE-initiated PI3K/Akt/MDR1 signaling pathway ( 104 ). They also showed that lucidone combined with gemcitabine reduces autophagy and promotes cell apoptosis through the HMGB1/RAGE/PI3K/Akt signaling pathway, thereby slowing down the development of pancreatic cancer ( 110 ). Currently, besides surgery, the main treatment methods for patients with exocrine pancreatic cancer in clinical practice are radiotherapy and chemotherapy, which can significantly activate autophagy in pancreatic cancer cells ( 135 , 136 ).…”
Section: Hmgb1/rage Axis and Tumor Developmentmentioning
confidence: 99%
“…Lucidone, a terpeneoid, inhibited autophagy via HMGB1/RAGE/PI3K/Akt signalling pathway in pancreatic cancer cells (Ref. 175 ). Celastrol induced autophagy by targeting AR/miR-101 and served as epigenetic regulator in prostate cancer cell lines (Ref.…”
Section: Natural Active Compounds In Longevity Interventionmentioning
confidence: 99%